Shake till you break – bilateral neck of humerus fracture post seizure - Christabel K; Dazlin Masdiana Sabardin; Tan, Toh Leong (Penerbit UKM, 2016)
Fractures may occur after an episode of seizures. Although rare, with a high index of suspicion and proper physical examination, delay of diagnosis and treatment can be avoided. We report a case of near missed bilateral proximal humerus fracture after an episode of generalized tonic-clonic seizure. A 58-year-old lady with a background history of epilepsy complained of generalized body ache after a generalized tonic-clonic seizure which happened few hours before presentation to our Emergency Department. On assessment, she was in pain and unable to move all four limbs. After given analgesia, patient was reassessed whereby she complained of bilateral shoulder stiffness and pain. Examination of the upper limbs revealed restricted range of movement in all directions with no shoulder squaring. X-ray showed bilateral proximal humerus fracture. Proximal humeral fractures rarely occur by itself following seizures; they are almost always associated with dislocation of the glenohumeral joint.